Carbohydrates as chiral templates - Stewart, Andrew O., author; Williams, Robert M., advisor (Colorado State University. Libraries, 1987)
Carbohydrates can serve as a source of functionalized asymmetric carbon atoms. The synthesis of a carbon fragment derived from 2-deoxy-glucose is described as an optically pure intermediate (34) for the synthesis of the antibiotic thienamycin. Natural products containing sugar moieties are direct targets for synthetic strategems utilizing carbohydrate precursors. The synthesis of naturally occurring C-glycosides from readily available sugars require carbon bond formation at the acetal carbon. Reported, herein, is methodology for the conversion of hemiacetals to the corresponding 2'-thiopyridyl acetals and subsequent metal activation toward nucleophilic displacement by carbon species resulting in efficient C-glycosidation. A glucosyl substrate (122) and two ribosyl substrates (147, 154) are described and their stereoselective reactions with different carbon nucleophiles are examined. The glucose substrate (122) shows general α-selectivity in carbon-carbon bond formation. The selectivity in the ribosyl substrates is quite good but, exhibits a large dependence on the particular nucleophile. The total synthesis of (+)- showdomycin is achieved employing a β-selective coupling of trimethoxybenzene and the ribosyl thioacetal (154) utilizing silver (I) activation. Preparation of other useful C-nucleoside precursors containing the required β-stereochemistry are reported. The use of these metal activated thiopyridyl acetals for intramolecular O-glycosidations are also investigated. Approaches to the [3.1.1) bycyclic oxetane of the thromboxane A2 nucleus using this methodology are examined. The use of a polymer bound mercury(II) salt (226) for activation of the thio-residue is shown to be useful in an intramolecular O-glycosidation resulting in the 1,5 anhydro-furanose (186). This polymer bound reagent should potentially represent an advantageous heterogeneous alternative to the homogeneous metal salts; particularly for glycosidations of sensitive substrates. In general, these thiopyridyl-acetals are stable precursors that may be readily activated by thiophilic metal salts for efficient nucleophilic substitution reactions.
Keywords: Carbohydrates; Chirality